2007
DOI: 10.1093/cercor/bhl161
|View full text |Cite
|
Sign up to set email alerts
|

Empathy for Pain and Touch in the Human Somatosensory Cortex

Abstract: Although feeling pain and touch has long been considered inherently private, recent neuroimaging and neurophysiological studies hint at the social implications of this experience. Here we used somatosensory-evoked potentials (SEPs) to investigate whether mere observation of painful and tactile stimuli delivered to a model would modulate neural activity in the somatic system of an onlooker. Viewing video clips showing pain and tactile stimuli delivered to others, respectively, increased and decreased the amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
272
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(308 citation statements)
references
References 67 publications
28
272
1
3
Order By: Relevance
“…Additionally, viewing another person's hand may cause social effects that seeing a rubber hand would not. Recent studies, for example, have found that seeing someone else being touched activates primary and secondary somatosensory cortex in a manner comparable to actual tactile perception (Blakemore et al, 2005;Bufalari et al, 2007;Keysers et al, 2004), suggesting a tactile homologue of the human mirror system (cf. Rizzolatti & Craighero, 2004).…”
Section: Subjective Reports Of Rubber Hand Illusionmentioning
confidence: 99%
“…Additionally, viewing another person's hand may cause social effects that seeing a rubber hand would not. Recent studies, for example, have found that seeing someone else being touched activates primary and secondary somatosensory cortex in a manner comparable to actual tactile perception (Blakemore et al, 2005;Bufalari et al, 2007;Keysers et al, 2004), suggesting a tactile homologue of the human mirror system (cf. Rizzolatti & Craighero, 2004).…”
Section: Subjective Reports Of Rubber Hand Illusionmentioning
confidence: 99%
“…Subsequent neuroimaging techniques and designs, more focused on sensory-motor functions, such as transcranial magnetic stimulation (Avenanti, Bueti, Galati, & Aglioti, 2005;Avenanti, Minio-Paluello, Bufalari, & Aglioti, 2006), magnetoencephalography (Cheng, Yang, Lin, Lee, & Decety, 2008), and electroencephalography (Bufalari, Aprile, Avenanti, Di Russo, & Aglioti, 2007;Jackson et al, 2007) demonstrated more consistently sensorymotor changes in relation with the mental representation of pain through pain observation.…”
Section: Decoding and Neurophysiological Reactions To Pain In Others mentioning
confidence: 99%
“…Some studies showed that only the affective component of the pain matrix are involved in empathy for pain, and thus that only emotional, not sensory, representations of pain are shared between self and others (Saarela et al, 2007;Singer et al, 2004). On the other hand, previous transcranial magnetic stimulation studies (Avenanti et al, 2005;Avenanti et al, 2006) and somatosensory evoked potential studies (Bufalari, Aprile, Avenanti, Di Russo, & Aglioti, 2007) highlighted the possible sensorimotor aspect of empathy for pain. In recent years, subsequent fMRI studies supported these findings, demonstrating that both affective and somatosensory components of the pain matrix are activated during watching of complex visual scenes (Benuzzi et al, 2008;Costantini et al, 2008;Han et al, 2009;Lamm, Batson, & Decety, 2007a).…”
Section: Brain Responses To Sounds Of Pain and Sufferingmentioning
confidence: 99%